2003
DOI: 10.1097/00005792-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Clinical Spectrum of Human Immunodeficiency Virus (HIV)-Related Oral Lesions in 1,000 Consecutive Patients

Abstract: In developing countries, the variations in the clinical spectrum of human immunodeficiency virus (HIV)-related oral lesions over time, and the possible effects of antiretroviral therapy, have not been described. In this study we evaluate the clinical spectrum of oral lesions in a series of HIV-infected patients when first examined at the acquired immunodeficiency syndrome (AIDS) clinic of a tertiary care institution in Mexico City, Mexico, and the changes observed over 12 years. All HIV-infected adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
136
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 55 publications
14
136
2
6
Order By: Relevance
“…Overall, yeasts were isolated from 59.9% of the subjects; of these, 32.7% presented with oral lesions by yeasts. This rate coincides with the 31.6% prevalence reported for oral candidiasis in Mexico during the last 12 years in HIV-infected patients (19). Moreover, only 12% of children infected with HIV/AIDS with oral colonization suffered from candidiasis.…”
supporting
confidence: 87%
“…Overall, yeasts were isolated from 59.9% of the subjects; of these, 32.7% presented with oral lesions by yeasts. This rate coincides with the 31.6% prevalence reported for oral candidiasis in Mexico during the last 12 years in HIV-infected patients (19). Moreover, only 12% of children infected with HIV/AIDS with oral colonization suffered from candidiasis.…”
supporting
confidence: 87%
“…2,14,[25][26][27][28][29] 60.4% of the patients with candidiasis were smokers and all of them were males. OC was highly associated with smoking, being 1.7 times more frequent in persons who smoke than in non-smokers (P <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of oral lesions has been shown to be significantly higher in individuals with a CD4+ count less than 200 cells/mm 3 and a viral load greater than 3000 copies/mL (Bravo et al, 2006;Greenspan et al, 2000;Tappuni & Fleming, 2001). The importance of oral lesions as clinical indicators of HIV infections and markers of clinical progression to AIDS has been demonstrated in many studies that reported their association with CD4+ depletion and high viral load (Bravo et al, 2006;Campo et al, 2002;Chattopadhyay et al, 2005;Glick et al, 1994;Greenspan et al, 2000;Patton, 2000;Ramírez-Amador et al, 2003;Shiboski et al, 2001). A comprehensive review of epidemiologic studies on HIV-related oral lesions reported from developed and developing countries over more than a decade, encompassing the pre-HAART and early-HAART period from 1986 to 2000, revealed oral candidiasis as the most common lesion found in all ages across the world (Patton et al, 2002).…”
Section: Epidemiology Of Hiv-associated Oral Manifestationsmentioning
confidence: 99%
“…The introduction of HAART has not only resulted in significant decline in mortality associated with HIV across the world, significant reduction was also seen in the prevalence of most AIDS-defining illnesses and opportunistic infections (Buchacz et al, 2010;Kaplan et al, 2000;Mocroft et al, 2004). Similarly, there has been a downward trend in the prevalence of oral opportunistic lesions in response to the use of HAART (Franceschi et al, 2008;Patton et al, 2000;Ramírez-Amador et al, 2003;Shiboski, 2002;Yang et al, 2010). Notable reduction was reported in the prevalence of two most common HIV-associated lesions, oral candidiasis and hairy leukoplakia (Eyeson et al, 2002;Nicolatou-Galitis et al, 2004;Patton et al, 2000;Ramírez-Amador et al, 2003).…”
Section: Epidemiology Of Hiv-associated Oral Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation